2010
DOI: 10.1200/jco.2009.23.1613
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's Lymphoma of the Breast

Abstract: A 49-year-old white woman presented with a 3-week history of right-breast redness and swelling after an insect bite. Physical examination revealed a 2 ϫ 1 cm nodule in the upper outer quadrant of the right breast, with diffuse tenderness, erythema, warmth, and peau d'orange (Fig 1 ) of the breast, and subcentimeter mobile painless adenopathy of the ipsilateral axilla. She was treated with oral cephalexin for a presumptive insect bite-related cellulitis. On follow-up physical examination 10 days later, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Breast lymphoma can rarely present with extended lymphedema, stimulating inflammatory breast carcinoma. To the best of our knowledge, three cases of HL with breast inflammatory presentation have been reported so far [14, 15, 20]. Our case shows similarities with the previous reports regarding the clinical appearance.…”
Section: Discussionsupporting
confidence: 87%
“…Breast lymphoma can rarely present with extended lymphedema, stimulating inflammatory breast carcinoma. To the best of our knowledge, three cases of HL with breast inflammatory presentation have been reported so far [14, 15, 20]. Our case shows similarities with the previous reports regarding the clinical appearance.…”
Section: Discussionsupporting
confidence: 87%
“…Some recent studies have shown that primary non-Hodgkin's lymphoma of the breast involving the axilla usually presents with the clinical appearance of inflammatory breast carcinoma without infiltration of the breast dermal lymphatics 6 . Tumor growth is usually accelerated 7 , which leads to enlarged tumors like the one described by Rahmat et al 8 . EBV has been postulated to play an important role in the pathogenesis of Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 95%
“…[6] Our patient also presented with axillary (bilateral), supraclavicular, cervical, and submandibular lymphadenopathy as well as oedema of the chest wall and upper limbs, similar to the earlier reported cases (rare cases). [7] In a series of 84 patients with primary breast lymphoma, most of the patients had painless palpable breast mass, only 10 (11.9%) had pain in the breast; while another 10 (11.9%) had their diagnoses during routine mammography as they did not have any palpable breast mass. [4] An overwhelming majority of patients presenting with breast lymphoma are middle aged and elderly women with preponderance in the right breast, though bilateral disease has been reported.…”
Section: Discussionmentioning
confidence: 98%